Effect of temperature on the phase behavior and microstructure of aggregates in SDS/Triton X-100/aH2O systems. (1st February 2017) - He, WeiYan; Liu, JinRong; Cao, ZhenZhu
ABSTRACT: The phase behavior and microstructure of a system containing polyoxyethylene tert-octylphenyl (Triton X-100), sodium dodecyl sulfate (SDS) and water were investigated using polarized optical microscopy (POM), differential scanning calorimetry (DSC) and small-angle X-ray diffraction (XRD). Phase-behavior study revealed that lamellar and hexagonal phases occurred in different compositions, and that lyotropic liquid crystal phases tended to form an H phase with increased Triton X-100 content. The effects of temperature on the phase behavior and microstructure of lyotropic liquid crystals were also studied. Heating induced a change from hexagonal to lamellar phase and from gel to hexagonal phase. POM and small-angle X-ray diffraction (SXRD) revealed that the phase-transition temperature of LLCs increased with increased Triton X-100 content, as further supported by DSC data.